Perlindungan Hukum bagi Pekerja Perempuan terhadap Waktu Kerja Berdasarkan Undang – Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan di Karawang: Studi Kasus di PT RMI - Ichsan Ramadan Bangun; Muhamad Abas; Yuniar Rahmatiar (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Legal protection for female workers regarding working hours is regulated by Law No. 13 of 2003 concerning Manpower, but remains Vulnerable to violations such as excessive working hourse and inadequate nighttime facilities. A case study at PT. TMI revealed obstacles stemming from workers’ lack of understanding, minimal company attention and suboptimal union support. The conclusion emphasizes the synergy between the three parties and the need for specific Regional Reglations to close regulatory gaps, through efforts to socialize the Collective Labor Agreement (PKB) and proactively respond to complaints.